Effect of Supplementation of Organic Acids on Nutrient Metabolizability and Economics of Quail Production - Bansod, Ashvini P.; Wankhede, S. M.; Waghe, S. B.; Shilwant, S. S.; Bhosale, S. R.; Surjagade, S. R. (International Journal of Livestock Research, 2021)
The present study was undertaken to assess the effect of supplementation of organic acids on Nutrient metabolizability trial and economics production of 300 Japanese quail divided into 5 treatment groups and each of 4 replicates with 15 birds in each replicate. The groups were T0- Control group, T1- T0 +0.20 % Acetic acid, T2- T0 +0.20 % Butyric acid, T3- T0 +0.20 % Propionic acid and T4 - T0 +0.20 % (Acetic acid, Butyric acid and Propionic acid). Metabolic trial of five days duration was conducted on 8 birds from each treatment at the end of experimental trial to study the dry matter digestibility and N- retention. The economics of production of Japanese quails was also calculated at the end of the experimental period. It is concluded that 0.2 % acetic acid is economically beneficial and also improve the retention of nutrient.